Implementation of the Communicative Approach in Arabic Language Learning at Madrasah Aliyah: A Descriptive Qualitative Study - Amanah Rahmawati; Kamalia Nurhikmah; Muhammad Arief Ramadhan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to describe the implementation of the communicative approach in Arabic language learning at Madrasah Aliyah. Specifically, the study seeks to examine how teachers apply the communicative approach in teaching and learning activities, analyze the strategies and methods used, assess students’ responses and engagement, identify supporting and inhibiting factors, and evaluate the effectiveness of the approach in improving students’ Arabic language skills. The research employs a qualitative descriptive method, focusing on an in-depth understanding of the learning process within the madrasah environment. Primary data were collected through observations, in-depth interviews, and documentation of Arabic teachers and students, while secondary data were obtained from documents such as lesson plans, syllabi, textbooks, and supporting literature. Data analysis was conducted through reduction, presentation, and conclusion drawing, validated using source and technique triangulation. The findings reveal that the implementation of the communicative approach in Madrasah Aliyah has been carried out by some teachers, but it is not yet optimal. Teachers understand the importance of communication skills in Arabic language learning but often still rely on conventional methods such as lecturing and text translation. Nevertheless, some teachers have attempted to apply communicative principles through activities such as role play, discussions, open Q&A sessions, and the use of audiovisual media. These strategies enhance student participation and motivation, particularly in speaking skills. Supporting factors include madrasah support, teacher enthusiasm, and student eagerness. Inhibiting factors involve limited time, lack of teacher training, and inadequate learning facilities. Overall, the communicative approach has proven capable of creating a more active, interactive, and contextual learning environment, and it has the potential to improve students’ communicative competence if supported by relevant learning systems and policies.